Using In Situ Symbiotic Seed Germination to Restore Over-collected Medicinal Orchids in Southwest China - Shao, Shi-Cheng; Burgess, Kevin S.; Cruse-Sanders, Jennifer M.; Liu, Qiang; Fan, Xu-Li; Huang, Hui; Gao, Jiang-Yun (Frontiers in Plant Science, 2017)
Due to increasing demand for medicinal and horticultural uses, the Orchidaceae is in urgent need of innovative and novel propagation techniques that address both market demand and conservation. Traditionally, restoration techniques have been centered on ex situ asymbiotic or symbiotic seed germination techniques that are not cost-effective, have limited genetic potential and often result in low survival rates in the field. Here, we propose a novel in situ advanced restoration-friendly program for the endangered epiphytic orchid species Dendrobium devonianum, in which a series of in situ symbiotic seed germination trials base on conspecific fungal isolates were conducted at two sites in Yunnan Province, China. We found that percentage germination varied among treatments and locations; control treatments (no inoculum) did not germinate at both sites. We found that the optimal treatment, having the highest in situ seed germination rate (0.94%1.44%) with no significant variation among sites, supported a warm, moist and fixed site that allowed for light penetration. When accounting for seed density, percentage germination was highest (2.78%2.35%) at low densities and did not vary among locations for the treatment that supported optimal conditions. Similarly for the same treatment, seed germination ranged from 0.24%5.87% among seasons but also did vary among sites. This study is the first to report on the cultivation and restoration of an endangered epiphytic orchid species by in situ symbiotic seed germination and is likely to have broad application to the horticulture and conservation of the Orchidaceae.